Is the internet a sufficient source of information on sarcoidosis? - Buschulte, Katharina; Höger, Philipp; Ganter, Claudia; Wijsenbeek, Marlies; Kahn, Nicolas; Kriegsmann, Katharina; Wilkens, Finn M.; Fisher, Jolene H.; Ryerson, Christopher J.; Herth, Felix; Kreuter, Michael (Frontiers in medicine, 2023)
IntroductionMany patients use the internet as a source of health information. Sarcoidosis is a complex disease, and internet resources have not yet been analyzed for reliability and content on sarcoidosis.AimsOur study aimed to investigate the content and the quality of information on sarcoidosis provided by internet resources.MethodsGoogle, Yahoo, and Bing were searched for the term “sarcoidosis,” and the first 200 hits were saved in each case. Those websites that met the inclusion criteria (English language, no registration fees, and relevant to sarcoidosis) were then analyzed by two independent investigators for readability, quality (HON, JAMA, and DISCERN), and content (25 predefined key facts) of the provided information.ResultsThe websites were most commonly scientific or governmental (n = 57, 46%), and the median time since the last update was 24 months. Quality was rated with a median JAMA score of 2 (1; 4) and a median overall DISCERN score of 2.4 (1.1; 4.1), both scores represent partially sufficient information. In total, 15% of websites had a HON certificate. Website content measured by the median key fact score was 19 (ranging from 2.5 to 25) with the lowest scores for acute vs. chronic course of the disease, screening for extrapulmonary disease, and diffuse body pain. Poor results were achieved in industry websites and blogs (p = 0.047) with significant differences regarding definition (p = 0.004) and evaluation (p = 0.021).DiscussionSarcoidosis-related content of internet resources is partially sufficient; however, several important aspects are frequently not addressed, and the quality of information is moderate. Future directions should focus on providing reliable and comprehensive information on sarcoidosis; physicians from different disciplines and patients including self-support groups should collaborate on achieving this.